Rede Mãe Paranaense : análise da implantação da rede no ambiente hospitalar e ambulatorial do Hospital Universitário Regional de Maringá - Remaile, Talita Tolentino Ronqui (2016)
The deployment of Paraná's Mother Network requires monitoring for effective control, compliance and adherence seeking to reduce maternal and infant mortality. The aim of this study was to monitor the connection between the points of attention and the line running guide advocated more attention to the care of black mothers and the performance of hospitals about the care of newborns. Therefore, we carried forward collections and retrospective analyzes of data records, prenatal card and Child Health Handbook 311 mother-child binomial met in the maternity of the Hospital Universitário Regional de Maringá (HUM) and 126 neonates received at the clinic intermediate risk CISAMUSEP. In HUM they were met 119 black pregnant women and 191 non-black. Only 61% pregnant women held seven or more prenatal consultations. The incompleteness index of notes of serological tests in prenatal card was very bad (≥ 50%), regardless of race / color and achievement rates of neonatal screening tests was excellent. Already the 126 neonates referred for intermediate-risk clinic, 80 were born in hospital school and they had high cesarean rates, low birth weight and increased incidence of classification as small for gestational age. The better quality indicators in achieving the neonatal screening tests as well. Only 20.6% neonates received home visits regardless of place of birth. However, neonates were quickly routed to the reference outpatient hospital at school than those born elsewhere. Overall, black pregnant women did not receive better prenatal care and incompleteness rates annotation of serological tests show the low quality of health care for all independent population of race / color. The neonates born at the hospital school were better assisted, but primary care has shortcomings and needs improvements in maternal and child care.